Response of Phytoplankton Assemblages From Naturally Acidic Coastal Ecosystems to Elevated pCO2 - Osma, Natalia; Latorre-Melín, Laura; Jacob, Bárbara; Contreras, Paulina Y.; von Dassow, Peter; Vargas, Cristian A. (Frontiers in Marine Science, 2020)
The interplay of coastal oceanographic processes usually results in partial pressures of CO2 (pCO2) higher than expected from the equilibrium with the atmosphere and even higher than those expected by the end of the century. Although this is a well-known situation, the natural variability of seawater chemistry at the locations from which tested organisms or communities originate is seldom considered in ocean acidification experiments. In this work, we aimed to evaluate the role of the carbonate chemistry dynamics in shaping the response of coastal phytoplankton communities to increased pCO2 levels. The study was conducted at two coastal ecosystems off Chile, the Valdivia River estuary and the coastal upwelling ecosystem in the Arauco Gulf. We characterized the seasonal variability (winter/summer) of the hydrographic conditions, the carbonate system parameters, and the phytoplankton community structure at both sites. The results showed that carbonate chemistry dynamics in the estuary were mainly related to seasonal changes in freshwater discharges, with acidic and corrosive conditions dominating in winter. In the Arauco Gulf, these conditions were observed in summer, mainly associated with the upwelling of cold and high pCO2 (>1000 atm) waters. Diatoms dominated the phytoplankton communities at both sites, yet the one in Valdivia was more diverse. Only certain phytoplankton groups in this latter ecosystem showed a significant correlations with the carbonate system parameters. When the impact of elevated pCO2 levels was investigated by pCO2 manipulation experiments, we did not observe any significant effect on the biomass of either of the two communities. Changes in the phytoplankton species composition and abundance during the incubations were related to other factors, such as competition and growth phases. Our findings highlight the importance of the natural variability of coastal ecosystems and the potential for local adaptation in determining responses of coastal phytoplankton communities to increased pCO2 levels.